Causal somatic mutations in urine DNA from persons with the CLOVES subgroup of the PIK3CA‐related overgrowth spectrum. Issue 5 (25th January 2018) - Michel, M.E.; Konczyk, D.J.; Yeung, K.S.; Murillo, R.; Vivero, M.P.; Hall, A.M.; Zurakowski, D.; Adams, D.; Gupta, A.; Huang, A.Y.; Chung, B.H.Y.; Warman, M.L.
Abstract : Congenital lipomatous overgrowth with vascular, epidermal, and skeletal (CLOVES) anomalies and Klippel‐Trenaunay (KTS) syndromes are caused by somatic gain‐of‐function mutations in PIK3CA, encoding a catalytic subunit of phosphoinositide 3‐kinase. Affected tissue is needed to find mutations, as mutant alleles are not detectable in blood. Because some patients with CLOVES develop Wilms tumor, we tested urine as a source of DNA for mutation detection. We extracted DNA from the urine of 17 and 24 individuals with CLOVES and KTS, respectively, and screened 5 common PIK3CA mutation hotspots using droplet digital polymerase chain reaction. Six of 17 CLOVES participants (35%) had mutant PIK3CA alleles in urine. Among 8 individuals in whom a mutation had been previously identified in affected tissue, 4 had the same mutant allele in the urine. One study participant with CLOVES had been treated for Wilms tumor. We detected the same PIK3CA mutation in her affected tissue, urine, and tumor, indicating Wilms tumors probably arise from PIK3CA mutant cells in patients with CLOVES. No urine sample from a participant with KTS had detectable PIK3CA mutations. We suggest that urine, which has the advantage of being collected non‐invasively, is useful when searching for mutations in individuals with CLOVES syndrome. Abstract :